Mechanisms of thrombosis in pancreatic ductal adenocarcinoma. Issue 1 (March 2022) - Campello, Elena; Bosh, Floris; Simion, Chiara; Spiezia, Luca; Simioni, Paolo
Abstract: Patients with pancreatic cancer have a very high risk of both venous and arterial thrombosis compared with other cancers, caused by a tumour-driven hypercoagulable state. Better understanding of pancreatic cancer-associated prothrombotic and proinflammatory mechanisms opens the door to controlling prothrombotic states, ideally, without affecting the overall haemostasis. This narrative review brings together currently available evidence on epidemiology and pathogenesis of thrombotic complications in pancreatic adenocarcinoma. We describe risk factors for thrombosis and established and novel mechanisms of hypercoagulability. Among novel pathways of hypercoagulability, the release of neutrophils extracellular traps (NETs) by activated neutrophils and the crucial role of extracellular vesicles (EV) in participating in platelet and coagulation activation were described. We also reported recent evidence on EV role in thrombin generation amplification through the activation of the intrinsic pathway, discussing potential molecules implicated in this process.